14th deadly sin [compact disc, unabridged] - Patterson, James, 1947-; Paetro, Maxine (Patterson, James, 1947- Women's murder club., 2015)
With a beautiful baby daughter and a devoted husband, Detective Lindsay Boxer can safely say that her life has never been better. In fact (for a change), things seem to be going well for all the members of the Women's Murder Club as they gather to celebrate San Francisco Medical Examiner Claire Washburn's birthday. But the party is cut short when Lindsay is called to a gruesome crime scene, where a woman has been murdered in broad daylight. As Lindsay investigates, shocking video footage of another crime surfaces. A video so horrific that it shakes the city to its core. Their faces obscured by masks, the cold-blooded criminals on the tape could be anyone--and now all of Lindsay's coworkers are suspects. As a rash of violence sweeps through San Francisco, and public fear and anger grows, Lindsay and her friends must risk their lives in the name of justice--before it's too late.